A Multi-Material CCALE-MOF Approach in Cylindrical Geometry (Communications in Computational Physics, 2018)
In this paper we present recent developments concerning a Cell-CenteredArbitrary Lagrangian Eulerian (CCALE) strategy using the Moment Of Fluid (MOF)interface reconstruction for the numerical simulation of multi-material compressiblefluid flows on unstructured grids in cylindrical geometries. Especially, our attentionis focused here on the following points. First, we propose a new formulation of thescheme used during the Lagrangian phase in the particular case of axisymmetric geometries. Then, the MOF method is considered for multi-interface reconstruction incylindrical geometry. Subsequently, a method devoted to the rezoning of polar meshesis detailed. Finally, a generalization of the hybrid remapping to cylindrical geometriesis presented. These explorations are validated by mean of several test cases using unstructured grid that clearly illustrate the robustness and accuracy of the new method.